Altered fatty acid metabolism and reduced stearoyl‐coenzyme a desaturase activity in asthma. Issue 11 (10th May 2017) - Rodriguez‐Perez, N.; Schiavi, E.; Frei, R.; Ferstl, R.; Wawrzyniak, P.; Smolinska, S.; Sokolowska, M.; Sievi, N.A.; Kohler, M.; Schmid‐Grendelmeier, P.; Michalovich, D.; Simpson, K.D.; et al.
Abstract: Background: Fatty acids and lipid mediator signaling play an important role in the pathogenesis of asthma, yet this area remains largely underexplored. The aims of this study were (i) to examine fatty acid levels and their metabolism in obese and nonobese asthma patients and (ii) to determine the functional effects of altered fatty acid metabolism in experimental models. Methods: Medium‐ and long‐chain fatty acid levels were quantified in serum from 161 human volunteers by LC/MS. Changes in stearoyl‐coenzyme A desaturase (SCD) expression and activity were evaluated in the ovalbumin (OVA) and house dust mite (HDM) murine models. Primary human bronchial epithelial cells from asthma patients and controls were evaluated for SCD expression and activity. Results: The serum desaturation index (an indirect measure of SCD) was significantly reduced in nonobese asthma patients and in the OVA murine model. SCD1 gene expression was significantly reduced within the lungs following OVA or HDM challenge. Inhibition of SCD in mice promoted airway hyper‐responsiveness. SCD1 expression was suppressed in bronchial epithelial cells from asthma patients. IL‐4 and IL‐13 reduced epithelial cell SCD1 expression. Inhibition of SCD reduced surfactant protein C expression and suppressed rhinovirus‐induced IP‐10 secretion, which was associated with increased viral titers. Conclusions: This is the first study to demonstrate decreased fatty acid desaturase activity in humans with asthma. Experimental models in mice and human epithelial cells suggest that inhibition of desaturase activity leads to airway hyper‐responsiveness and reduced antiviral defense. SCD may represent a new target for therapeutic intervention in asthma patients.